An court action for payment from the National Health Fund for health benefits provided in emergency – selected practical issues - Damian Wąsik; Natalia Wąsik; Tomasz Kuczur (Prawo Budżetowe Państwa i Samorządu)
The publication describes the problems of payment seeking by healthcare institutions from the National Health Fund for the so-called “life-saving health benefits”. Issues, which are discussed, include the possibility of health benefits financing in the context of the contract’s limits, the burden of proof to provide the health benefits in emergencies, and the necessary of consult experts on these issues in the context of the conditions of Article 248 § 1 Polish Civil Procedure Code.